Analisis Kebutuhan Bahan Ajar Aljabar Linier Bagi Mahasiswa Jurusan Sistem Komputer - Nia Maharani (UNIB Press, 2022)
Linear algebra is a compulsory subject in Computer Systems which has 3 credits. This course is a new course in semester 2 and includes material on vector concepts in R2 (two dimensions) and R3 (three dimension), Euclidian vectors, general vector spaces, inner product spaces, orthonormals and equations of vectors. The teaching materials used were PPT slides compiled from various sources, both from textbooks and from the internet. This study aims to determine the linear algebra material that needs to be developed for students majoring in Computer Systems in offline learning. The subjects in this research were Computer Systems students who are taking linear algebra courses for the 2021/2022 academic year. Data were collected in the form of student test results and questionnaires given openly and then analyzed descriptively qualitatively. The results of the study indicate the need for teaching materials that are easily understood by students in solving problems and in accordance with current technological advances. Teaching materials in the form of e-modules can be used as an alternative to support learning in the classroom and can be accessed at any time.